Pengaruh Kualitas Pelayanan, Harga Dan Atmosfer Café Terhadap Keputusan Pembelian Pada Nabs Café Pacet – Mojokerto - Nickofwan Andysetya Fernanda; Imam Baidlowi; Agoes Hadi Poernomo (Lokawati : Jurnal Penelitian Manajemen dan Inovasi Riset, 2023)
In the increasingly more business cafe competition in the era of today, every businessman or businessman in the field of beverages and food must be able to maintain the continuity of the business they run. In order to survive and be successful in the field of food and beverages, an entrepreneur must be able to consider from what makes consumers interested in stopping by the café. This study aims to determine the effect of the quality of service, price and atmosphere of café on purchasing decisions (case studies at Nabs Café in Mojokerto City). This study uses a quantitative method with a sample of 100 respondents with the help of data processing IBM SPSS 26. The results of this study indicate that partially the variable service quality has a positive and significant effect on purchasing decisions, partially the price variable has a positive and significant effect on purchasing decisions, partially the atmospheric café variable has a positive and significant effect on purchasing decisions, simultaneously the effect of service quality, price and atmosphere of the café has a positive and significant effect on purchasing decisions (case studies in NABS Café in Mojokerto City).